EPLINα controls integrin recycling from Rab21 endosomes to drive breast cancer cell migration - Jäntti, Niklas Z.; Moreno-Layseca, Paulina; Chastney, Megan R.; Dibus, Michal; Conway, James R.W.; Leppänen, Veli-Matti; Hamidi, Hellyeh; Eylmann, Kathrin; Oliveira-Ferrer, Leticia; Veltel, Stefan; Ivaska, Johanna (Elsevier BV, 2026)
Epithelial protein lost in neoplasm (EPLIN), an actin-binding protein, has been described as both a tumor promoter and tumor suppressor in different cancers. The roles of EPLIN isoforms (α/β) remain largely unknown and could explain these opposing views. We observed distinct EPLIN isoform localization in breast cancer cells; EPLINα is recruited to actin in plasma membrane ruffles and endosomes, while EPLINβ resides on stress fibers. EPLINα localizes to early endosomes in an actin-dependent manner, where it interacts with Rab21, an established regulator of β1-integrin endosomal trafficking. This supports β1-integrin recycling and cell migration. Using proximity biotinylation (BioID), we identified coronin 1C as an EPLIN-proximal protein, which also localizes at Rab21-containing endosomes and controls integrin recycling downstream of EPLINα. EPLINα expression was linked to increased breast cancer cell motility, and a high EPLINα-to-EPLINβ ratio correlated with a mesenchymal phenotype in patient samples. Our work identifies previously unknown EPLIN-isoform-specific functions relevant to breast cancer and beyond.